Research on Coordination Strategy of Data Transmission Scheduling and Control in WTB Bus Protocol Network - Zhishuai CHEN; Xiang LIU; Rui LIU; Fanyan XUE (机车电传动)
Based on the research of WTB bus protocol network data transmission characteristics, a PMTS scheduling strategy for coordinated control of periodic data and aperiodic data transmission was proposed. Using the scheduling theory and control strategy of real-time control systems, a periodic data scheduling and polling mechanism was constructed in real time, and a non-periodic data dynamic preemption scheduling control method is designed so as to achieve coordinated control and scheduling of network data transmission. The WTB bus protocol network data transmission experimental platform was set up, and the PMTS scheduling strategy was applied to the independently designed train communication gateway system. The result shows that the scheduling strategy could flexibly allocate the normal operation cycle of the WTB bus network grouping, and the cooperation between the underlying data transmission and the upper protocol was realized.